Defects and moisture problems in buildings from historical city centres : a case study in Portugal - Lourenço, Paulo B. (2006)
Conservation of ancient buildings is a major issue for modern societies, both from economical and cultural viewpoints. Information about the ancient built heritage is vital to plan adequate remedial measures. Using a historic centre in Portugal as a case study, this paper presents an extensive survey of building typology and materials, damage in the building envelope, indoor survey of damage, and measurements in indoor air temperature and relative humidity. Water-related problems can be confirmed as the single most important defect, which are combined with inadequate sun exposure, ventilation and heating, and excessive moisture indoor production. Extremely low temperatures, high humidity and presence of mould therefore compromise the indoor quality of life of the inhabitants, being urgent repair needed at many levels.